Modeling nitrate contamination of groundwater in irrigated lands - Marcos, John Mark A. (2012)
Groundwater is the major source of water supply in rural areas of developing countries. In these communities, agriculture practices pose a risk of contaminating groundwater as some chemical species including nitrates have the potential to leach into the water table. In this study, a transient, three-dimensional groundwater flow and mass transport was solved using the finite element method via the solute solver FEMWATER to predict nitrate contamination in the field. Boundary conditions for flow and transport simulation was applied based on available field data and measurements reported in literature. The model efficiency and accuracy were measured based on coefficient of determination (R2) and root mean squared error (RMSE). The model shows acceptable fit with observed field samplings (R2=0.851 and RMSE=0.166mg/L). The five-year model simulation exhibited an increasing trend of nitrate contamination that gradually approaches the prescribed value of the Department of Environment and Natural Resources (DENR) for potable water. Sensitivity analysis indicated that nitrate concentrations are highly influenced by decay rate and mass of fertilizer applied. The developed model can be further improved and used as a prediction tool in long term monitoring of groundwater nitrate contamination.